2022
DOI: 10.1016/j.amjmed.2021.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Risk Following Systemic Fluconazole or Topical Azoles in Patients with Atrial Fibrillation on Apixaban, Rivaroxaban, or Dabigatran

Abstract: BACKGROUND: Bleeding safety in relation to use of systemic fluconazole and topical azoles among patients with atrial fibrillation treated with apixaban, rivaroxaban, or dabigatran is insufficiently explored, despite clinical relevance and several reports suggesting associations. METHODS: Using nationwide Danish registers, we identified patients with atrial fibrillation initiated on apixaban, rivaroxaban, or dabigatran from 2012-2018. We investigated associations between bleeding incidents and systemic fluconaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…This analysis observed that apixaban users had a higher risk of bleeding following exposure to fluconazole (OR 3.5) while no differences were found among rivaroxaban and dabigatran users [85]. Topical azole exposure did not increase bleeding risk with any DOACs [85].…”
Section: Potential Drug-drug Interaction With Antibiotics and Antifun...mentioning
confidence: 86%
See 2 more Smart Citations
“…This analysis observed that apixaban users had a higher risk of bleeding following exposure to fluconazole (OR 3.5) while no differences were found among rivaroxaban and dabigatran users [85]. Topical azole exposure did not increase bleeding risk with any DOACs [85].…”
Section: Potential Drug-drug Interaction With Antibiotics and Antifun...mentioning
confidence: 86%
“…Thus, patients treated with rivaroxaban in combination with multiple modulators of P-gp (cyclosporin) and CYP3A4 (fluconazole) require particular care. The clinical impact of the combination of therapy with DOACs and fluconazole has been recently investigated by using the nationwide Danish registers [85]. This analysis observed that apixaban users had a higher risk of bleeding following exposure to fluconazole (OR 3.5) while no differences were found among rivaroxaban and dabigatran users [85].…”
Section: Potential Drug-drug Interaction With Antibiotics and Antifun...mentioning
confidence: 99%
See 1 more Smart Citation
“…Direct oral anticoagulants (DOACs) have fewer drug interactions than warfarin, but interactions do occur. In a large series involving nearly 100,000 individuals receiving a DOAC, individuals receiving apixaban plus fluconazole, a moderate inhibitor of the P450 cytochrome CYP3A4, had a 3.5-fold increased risk of bleeding compared with periods when they were receiving apixaban without fluconazole 1. The increase was greatest in gastrointestinal bleeding requiring hospitalization.…”
Section: Family Medicine — Adult General Internal Medicinementioning
confidence: 99%
“…In a large series involving nearly 100,000 individuals receiving a DOAC, individuals receiving apixaban plus fl uconazole, a moderate inhibitor of the P450 cytochrome CYP3A4, had a 3.5-fold increased risk of bleeding compared with periods when they were receiving apixaban without fl uconazole. 1 The increase was greatest in gastrointestinal bleeding requiring hospitalization. The risk was only seen with systemic fl uconazole plus apixaban; it did not occur with topical fl uconazole plus apixaban or systemic fl uconazole plus another DOAC.…”
Section: )mentioning
confidence: 99%